Personification and iconography of death in ancient Greece - Crespo Güemes, Emilio (2020)
This article brings together mentions and representations of the personification of Death in literature and the visual arts from Homer to the beginning of the Hellenistic era. It focuses on Homer's Iliad, Hesiod's Theogony, tragedy and the famous crater painted by Euphronios, which represents the moment when Death and Sleep, in the presence of Hermes, raise Sarpedon's corpse from the ground to transport it to his native land. The article argues that the scene of the mythical transfer of Sarpedon's body by Death and Sleep was reinterpreted as the repatriation of the body of any Athenian citizen who had died abroad, which the law mentioned by Thucydides in his History of the Peloponnesian War imposed.